Statistical Brief on the National Agricultural Research System of Botswana - International Service for National Agricultural Research (International Service for National Agricultural Research, 1993)
The primary purpose of this brief is to provide various statistical and institutional details on the development and current status of the public agricultural research system in Botswana. This information has been collected and presented in a systematic way in order to inform and thereby improve research policy formulation with regard to the NARS of Botswana. Most importantly, these data are assembled and reported in a way that makes them directly comparable with the data presented in the other country briefs in this series. And because institutions take time to develop and there are often considerable lags in the agricultural research process, it is necessary for many analytical and policy purposes to have access to longer-run series of data.